Investigation of exact traveling wave solution for the (2+1) dimensional nonlinear evolution equations via modified extended tanh-function method - Kumar, Dipankar; Sarker, Prodip (International Journal of Physical Research, 2016)
In this study, we have implemented the modified extended tanh-function method to obtain the exact travelling wave solutions for the general (2+1)-dimensional nonlinear evolution equations. By using this method, some travelling wave solutions are successfully obtained and which have been expressed by the trigonometric, hyperbolic and rational functions. These obtained solutions are an appropriate and desirable for instructive specific nonlinear physical phenomena in genuinely nonlinear dynamical systems. The method is an efficient and reliable mathematical tool for solving many nonlinear evolution equations arising in science and engineering problems.